2019
DOI: 10.1038/s41598-019-47169-6
|View full text |Cite
|
Sign up to set email alerts
|

Early-life factors are associated with waist circumference and type 2 diabetes among Ghanaian adults: The RODAM Study

Abstract: Early-life experiences may fuel the emergence of obesity and type 2 diabetes among African populations. We evaluated childhood socio-economic status (SES) and childhood nutritional status as risk factors for increased waist circumference and type 2 diabetes among Ghanaian adults. In the multi-center, cross-sectional Research on Obesity and Diabetes among African Migrants (RODAM) Study, we calculated associations (adjusted for demographics and lifestyle) of parental education and anthropometric markers of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…Gender is also important when deciding how to deal with other chronic conditions such as, for example, arterial hypertension [34]. Poor socio-economic status could be even more important in determining the incidence of T2D and its phenotypic manifestations [35,36]. However, despite this, we have demonstrated that the pattern of chronic comorbidity still shows differences in different ethnic groups, after having taken into account socio-economic conditions [37].…”
Section: Discussionmentioning
confidence: 79%
“…Gender is also important when deciding how to deal with other chronic conditions such as, for example, arterial hypertension [34]. Poor socio-economic status could be even more important in determining the incidence of T2D and its phenotypic manifestations [35,36]. However, despite this, we have demonstrated that the pattern of chronic comorbidity still shows differences in different ethnic groups, after having taken into account socio-economic conditions [37].…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, proxy measures are useful even when DXA is available but cannot be justified at every follow-up visit. Therefore, and after firm association of estimators based on waist circumference and trunk fat, we recommend that the studied estimators be used because of their safety, simplicity [61], known low variability [62] and good correlation with CT and MRI [63] when assessing metabolically unhealthy fat accumulation [3,64] and furthermore to increase precision by considering sex [55] and age if assessing a diverse sample [65,66,67].…”
Section: Blood Pressurementioning
confidence: 99%
“…Com relação ao perfil lipídico a maioria das pacientes apresentaram valores dentro da normalidade. De fato, tem sido relatado que os principais fatores de risco associados ao desenvolvimento das comorbidades associadas ao DM2 são os maus hábitos alimentares (FERREIRA et al, 2014;MOREIRA et al, 2018), o sedentarismo (BENITE-RIBEIRO et al, 2020;DOS SANTOS et al, 2018;DOS SANTOS et al, 2015b), o aumento da massa corporal relacionada à deposição de gordura, principalmente na região abdominal (BARROSO et al, 2017;DANQUAH et al, 2019), e a dislipidemia (MALTA et al, 2011;BARROSO et al, 2017;MAGKOS;HJORTH;ASTRUP, 2020). O acúmulo de lipídeos ectópicos quando associado com a capacidade reduzida da β-oxidação celular caracteriza um processo denominado lipotoxicidade (ALWAHSH et al, 2017;DE CASTRO et al, 2013;DISSARD et al, 2013;ERTUNC;HOTAMISLIGIL, 2016;FU et al, 2009).…”
Section: Avaliação Da Adesão Ao Tratamento Não Medicamentosounclassified